The sacred town of Sankhu : the anthropology of Newar ritual, religion and society in Nepal - Shrestha, Bal Gopal, 1959- (Cambridge Scholars, 2012)
This book presents a detailed view on Newar society and culture, its socio-economic, socio-religious and ritual aspects, concentrating on a single Newar town of Sankhu in the Valley of Nepal. The foundation of the town of Sankhu is attributed to the godde.